An insight into piscidins: The discovery, modulation and bioactivity of greater amberjack, Seriola dumerili, piscidin. (October 2019) - Milne, Douglas John; Fernández-Montero, Álvaro; Gundappa, Manu K.; Wang, Tiehui; Acosta, Félix; Torrecillas, Silvia; Montero, Daniel; Zou, Jun; Sweetman, John; Secombes, Christopher John
Highlights: A novel piscidin active peptide was cloned in the greater amberjack, Seriola dumerili . Homology and phylogenetic analysis show it is a group 3 piscidin. It is expressed constitutively at immune sites, with highest transcript levels in the spleen and gut. Modulated expression was shown in vivo ad in vitro using PAMPs. Dietary modulation was also possible, using prebiotics (MOS, cMOS). Greater amberjack piscidin has bacteriostatic activity to a range of Gram positive and Gram negative fish pathogens. Abstract: Antimicrobial peptides (AMPs) play an important role in the innate immune response of vertebrates by creating a hostile environment for any invading pathogens. Piscidins are potent teleost specific AMPs, which have a broad spectrum activity. We have identified a novel piscidin active peptide, in the greater amberjack, Seriola dumerili, that consists of 25 aa, which forms an amphipathic helix with distinct hydrophobic and positively charged regions. Following homology and phylogenetic analysis the greater amberjack piscidin was deemed to belong to the group 3 family of piscidins. Piscidin was expressed constitutively at immune sites, with transcript level highest in the spleen and gut, at an intermediate level in the gills and lowest in the head kidney. Following in vivo stimulation with PAMPs (poly I:C, LPS and flagellin) piscidin transcript level increased in gills in response to flagellin, in gut and spleen in response to poly I:C, and in head kidney in response to poly I:C, LPS and flagellin. Head kidney and spleen cells were then isolated from greater amberjack and incubated with each of the PAMPs for 4, 12 and 24 h. Piscidin expression was unchanged at 4 and 12 h post PAMP stimulation in head kidney cells but at 24 h transcript level was markedly upregulated compared to control (unstimulated) cells, especially with the bacterial PAMPs. In contrast, spleen cells upregulated piscidin expression by 4 h post stimulation with poly I:C and flagellin, and remained upregulated to 24 h with flagellin exposure, but had returned to baseline levels by 12 h using poly I:C. To determine if piscidin expression could be modulated by diet, greater amberjack were fed diets supplemented with MOS and cMOS for 30 days when transcript level was determined. It was found that MOS supplemented diets increased expression in the spleen, cMOS supplemented diets upregulated transcript levels in the gills and head kidney, whilst a diet containing both MOS and cMOS upregulated transcript in the gut, when compared to fish fed the control diet. Finally, a synthetic greater amberjack piscidin was produced and showed bacteriostatic activity against a number of bacterial strains, including both Gram positive and Gram negative fish pathogens.